PENERAPAN TEHNIK PERAMALAN UNTUK MEMBERIKAN KEUNGGULAN BERSAING - Andi Widiawati (AkMen JURNAL ILMIAH, 2014)
Every day, managers make and take decisions in the absence of knowing exactly what will happen in the future. Forecasting is a tool that can help managers to create and predict future events. Forecasting is an important part of the operations management function. Forecasting demand direct the production, capacity, and enterprise scheduling systems, as well as affect the functioning of financial, marketing and human resources planning. Various forecasting techniques that can be taken to help make forecasting, ie forecasting qualitative and quantitative forecasting. Forecasting using a qualitative judgment, experience, feelings, and factors which are difficult to measure. Quantitative forecasting using past data, cause and effect for the projected future demand.